The Paper-Toss Test: enhancing bedside recognition of corticobasal syndrome - Lueg, Gero; Duning, Thomas; Hobert, Markus A.; Rösler, Alexander; Peranovic, Sara; Wirth, Rainer; Krämer, Julia (Frontiers in Neurology, 2025)
IntroductionThe diagnosis of corticobasal syndrome (CBS) is challenging due to its clinical overlap with other neurodegenerative disorders. Ideomotor apraxia is a core feature of CBS and often presents asymmetrically, but is often under-recognized in the clinical setting.MethodsThe “Paper-Toss Test” (PTT) is administered to a video-based case series of four patients with different CBS pathologies (Alzheimer’s disease, progressive supranuclear palsy, and corticobasal degeneration) and involves instructions to throw a paper ball with each hand. A positive test result is indicated by the presence of specific performance deficits of the patient’s affected side such as an absent or delayed release of the paper ball or an interrupted throwing motion.ResultsAll patients exhibited a positive PTT, independent of the underlying cause of CBS.DiscussionThis study proposes the PTT (Paper-Toss Test) as a bedside tool for the detection of unilateral ideomotor apraxia, facilitating the diagnosis of CBS. These deficits correspond to the known impairments in transitive gestures and disturbances of the neuronal apraxia network in CBS patients. These results support further investigation and validation of the PTT in clinical practice.